Designing a stated choice experiment: The value of a qualitative process - Mirja Elisabeth Kløjgaard; Mickael Bech; Rikke Søgaard (Journal of Choice Modelling, 2012)
Designing a stated or discrete choice experiment (DCE) involves a process of developing, testing and optimizing the experiment questionnaire. This process is important for the success of the experiment and the validity of the results, but it is often not reported thoroughly. In the field of health care, one faces challenges in relation to what makes sense both for the respondent and what has clinical relevance, especially in situations with little evidence and unclear choices, where the decision making process is not clear or informed. This is the case for degenerative spine diseases, where the selection of candidates for surgical rather than non-surgical treatment has been widely discussed and where surgery rates accordingly vary across settings. In the present work, we demonstrated how the qualitative process significantly impacted and guided the design, and it was clear that a less thorough qualitative process would have resulted in a less useable and valid design. To elicit relevant attributes and levels for a DCE, fieldwork in clinical departments in Danish hospitals was performed and has been supplemented by qualitative interviews with patients and doctors. Systematic and thorough qualitative investigation of the decision context relevant attributes and levels and appropriate framing appears valuable in the process of designing a DCE for quantitative pilot testing.
Keywords: 330; design; discrete choice experiment; qualitative methods; attribute and level selection